Effects of controlled dual growth factor delivery on bone regeneration following composite bone-muscle injury. (15th September 2020) - Subbiah, Ramesh; Cheng, Albert; Ruehle, Marissa A.; Hettiaratchi, Marian H.; Bertassoni, Luiz E.; Guldberg, Robert E.
Abstract: The objective of this study was to investigate the controlled release of two growth factors (BMP-2 and VEGF) as a treatment strategy for bone healing in clinically challenging composite injuries, consisting of a femoral segmental bone defect and volumetric muscle loss. This is the first investigation of dual growth factor delivery in a composite injury model using an injectable delivery system consisting of heparin microparticles and alginate gel. The loading efficiency of growth factors into these biomaterials was found to be >90%, revealing a strong affinity of VEGF and BMP-2 to heparin and alginate. The system could achieve simultaneous or tunable release of VEGF and BMP-2 by varying the loading strategy. Single growth factor delivery (VEGF or BMP-2 alone) significantly enhanced vascular growth in vitro . However, no synergistic effect was observed for dual growth factor (BMP-2 + VEGF) delivery in vitro . Effective bone healing was achieved in all treatment groups (BMP-2, simultaneous or tunable delivery of BMP-2 and VEGF) in the composite injury model. The mechanics of the regenerated bone reached a maximum strength of ~52% of intact bone with tunable delivery of VEGF and BMP-2. Overall, simultaneous or tunable co-delivery of low-dose BMP-2 and VEGF failed to fully restore the mechanics of bone in this injury model. Given the severity of the composite injury, VEGF alone may not be sufficient to establish mature and stable blood vessels when compared with previous studies co-delivering BMP-2+VEGF enhanced bone tissue regeneration. Hence, future studies are warranted to develop an alternative treatment strategy focusing on better control over growth factor dose, spatiotemporal delivery, and additional growth factors to regenerate fully functional bone tissue. Statement of Significance: We have developed an injectable delivery system consisting of heparin microparticles and an alginate hydrogel that is capable of delivering multiple growth factors in a tunable manner. We used this delivery system to deliver BMP-2 and VEGF in a rodent model of composite bone-muscle injury that mimics clinical type III open fractures. An advanced treatment strategy is necessary for these injuries in order to avoid the negative side effects of high doses of growth factors and because it has been shown that the addition of a muscle injury in this model attenuates the bone regenerative effect of BMP-2. This is the first study to test the effects of dual growth factor delivery (BMP-2/VEGF) on bone healing in a composite bone-muscle injury model and is expected to open up new directions in protein delivery for regenerative medicine. Graphical abstract: Image, graphical abstract